ENHANCING STUDENT LEARNING ENGAGEMENT THROUGH BLENDED LEARNING WITH LECTURES AND MIND MAP MEDIA - Megananda, Almas Wilda Pradnya (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2025)
The problem of low student learning engagement in the subject of Akidah Akhlak, especially in the material of Adab Berteman, is the main focus of this study. The results of initial observations in class IV Al Qudus MIN 4 Jombang showed that most students tended to be passive, did not understand the values of adab, and had not shown active participation in learning. This study aims to increase student learning engagement through the application of the Blended Learning method which combines a lecture approach with the use of mind map media as a visual aid. This study uses a qualitative approach with the type of Classroom Action Research (CAR) model Kemmis and McTaggart which is carried out in two cycles. Each cycle includes the stages of planning, implementation, observation, and reflection. The subjects of the study consisted of 36 students of class IV Al Qudus. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study showed a significant increase in student learning engagement, the ability to understand the contents of the material, and active participation in discussions and making mind maps. In cycle I, student involvement was still limited, but in cycle II more than 85% of students showed increased participation and were able to compile and explain mind maps with the theme of Adab Berteman independently or in groups. The conclusion of this study is that the Blended Learning method is effective in increasing student learning engagement and helping internalize the values of manners in learning Akidah Akhlak.